Journey to the Center of the Fetal Brain: Environmental Exposures and Autophagy - Lei, Jun; Calvo, Pilar; Vigh, Richard; Burd, Irina (Frontiers in Cellular Neuroscience, 2018)
Fetal brain development is known to be affected by adverse environmental exposures during pregnancy, including infection, inflammation, hypoxia, alcohol, starvation and toxins. These exposures are thought to alter autophagy activity in the fetal brain, leading to adverse perinatal outcomes, such as cognitive and sensorimotor deficits. This review introduces the physiologic autophagy pathways in the fetal brain. Next, methods to detect and monitor fetal brain autophagy activity are outlined. An additional discussion explores possible mechanisms by which environmental exposures during pregnancy alter fetal brain autophagy activity. In the final section, a correlation of fetal autophagy activity with the observed postnatal phenotype is attempted. Our main purpose is to provide the current understanding or a lack thereof mechanisms on autophagy, underlying the fetal brain injury exposed to environmental insults.